2017
DOI: 10.1002/dvdy.24559
|View full text |Cite
|
Sign up to set email alerts
|

HMGB2 expression is associated with transition from a quiescent to an activated state of adult neural stem cells

Abstract: Background: Although quiescent neural stem cells (NSCs) in the adult hippocampus proliferate in response to neurogenic stimuli and subsequently give rise to new neurons continuously throughout life, misregulation of NSCs in pathological conditions, including aging, leads to the impairment of learning and memory. High mobility group B family 1 (HMGB1) and HMGB2, HMG family proteins that function as transcriptional activators through the modulation of chromatin structure, have been assumed to play some role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…[ 96 ]. A number of them are known to be associated with NSC development and function such as SMOC1 [ 101 ], SOX2, CRABP1 [ 104 ], CSRP2 [ 106 ], CRABP2 [ 143 ], CTNND2 [ 144 ], SOX3, MSI1 [ 145 ], HMGB2 [ 146 ], and LAMB1 [ 147 ]. Moreover, among the 129 upregulated STSPs at the NSC (d8) stage, 36 STSPs (PS 3) show a transient trend as their abundances decrease while approaching the NPC (d12) state.…”
Section: Data Descriptionmentioning
confidence: 99%
“…[ 96 ]. A number of them are known to be associated with NSC development and function such as SMOC1 [ 101 ], SOX2, CRABP1 [ 104 ], CSRP2 [ 106 ], CRABP2 [ 143 ], CTNND2 [ 144 ], SOX3, MSI1 [ 145 ], HMGB2 [ 146 ], and LAMB1 [ 147 ]. Moreover, among the 129 upregulated STSPs at the NSC (d8) stage, 36 STSPs (PS 3) show a transient trend as their abundances decrease while approaching the NPC (d12) state.…”
Section: Data Descriptionmentioning
confidence: 99%
“…HMGB1 and HMGB2 were listed as especially over-expressed during the activation of qNSCs in the adult dentate gyrus (Shin et al, 2015 ). Addittionally, HMGB2 expression is strongly associated with transition from the quiescent to the proliferative state of NSCs (Kimura et al, 2018 ).…”
Section: Factors Regulating Normal Cell Quiescencementioning
confidence: 99%
“…Recent findings suggest that HMGB proteins could differentially affect neurogenesis through the regulation of neural stem cell (NSC) proliferation and survival [ 13 , 33 , 34 ]. Previous studies demonstrated the involvement of SOX2 and PAX6 (markers of stem/progenitor cell proliferation and neurogenesis) in the developing human nervous system [ 35 ] and the derivation of human neural stem cells (hNSCs) from hESCs [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although their DNA binding preferences are similar, their protein binding partners are mostly distinct [ 4 , 52 ]. HMGB1 is indispensable for life, whereas HMGB2 −/− knockout mice are able to survive with reduced fertility and spermatogenesis defects [ 34 , 53 , 54 ]. HMGB1 expression is ubiquitous, but HMGB2 is widely expressed during embryogenesis [ 54 ] and also in adults, mainly in the lymphoid organs and testes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation